Influence of Strategic Food Price on Inflation in Medan City - Rafinda, M. Syarif; Novita, Desi; Ryansyah, Kus (PT Inovasi Pratama Internasional, 2024)
This study aims to determine how much influence strategic food prices have on inflation in Medan City. The data collection for this research was sourced from several related agencies, such as the Central Statistics Agency for Medan Province, Bank Indonesia, the Food Crops and Horticulture Office for North Sumatra Province, and other literature. The data analysis method used in this study is to use the Data Analysis Matrix. The results of the study show that the development of food commodity prices in Medan City from January 2018 to July 2021 generally has a fluctuating tendency.